1992
DOI: 10.1016/s0022-5347(17)37462-1
|View full text |Cite
|
Sign up to set email alerts
|

Variability and Circadian Changes in Home Uroflowmetry in Patients with Benign Prostatic Hyperplasia Compared to Normal Controls

Abstract: We evaluated the variability and circadian changes in consecutive measurements of home uroflowmetry in 32 patients with symptomatic benign prostatic hyperplasia (BPH) and 16 healthy men. In the BPH group 476 uroflow measurements were recorded during 24 to 72 hours (mean 14.9 measurements per patient), and the controls produced 100 flow recordings (mean 6.25 measurements per participant). Great variability between consecutive peak flow rates was observed in the BPH group, ranging from at least 1 standard deviat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
1
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(56 citation statements)
references
References 7 publications
2
52
1
1
Order By: Relevance
“…The finding of increased voided volumes during night time has already been observed. Golomb et al, 3 however, observed lower maximum and adjusted maximum flow rates between midnight and noon; we found a significant difference of average and maximum flow rates between midnight and 0600 hours, that is between sleep hours and the time of normal daily activities. Our study group is representative enough, being the largest so far to confirm the finding of changes in voiding patterns in relationship to the time of the day.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…The finding of increased voided volumes during night time has already been observed. Golomb et al, 3 however, observed lower maximum and adjusted maximum flow rates between midnight and noon; we found a significant difference of average and maximum flow rates between midnight and 0600 hours, that is between sleep hours and the time of normal daily activities. Our study group is representative enough, being the largest so far to confirm the finding of changes in voiding patterns in relationship to the time of the day.…”
Section: Discussioncontrasting
confidence: 62%
“…Some authors, besides, found variability between consecutive flow measurements and circadian changes in various voiding parameters, and particularly in maximum flow rate. 2,3 Therefore, any decision based on a single-flow measurement is questionable, since a natural situation is recommended when using uroflowmetry to depict a patient's normal voiding pattern. Data from a homebased portable flowmeter may accomplish this objective.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with voiding symptoms (21, 66%) had a median (range) American Urological Association symptom score of 17 (4-34), a Bother score of 16 , and Quality of Life score of 3 (1)(2)(3)(4)(5)(6). The mean Q max was 16.9 (4.5-36.9) and 13.3 (4.5-39.4) mL/s before and after cystoscopy, respectively ( P = 0.029).…”
Section: Resultsmentioning
confidence: 99%
“…The upper limit of bladder capacity varies in each patient but it is generally accepted to have the patient urinate when he/she feels the urge to do so with no delay. Variability in interpreting the uroflow graphs and Q max values has been discussed; Golomb et al [6] reported variability in Q max relating to circadian changes in a series of 32 patients, with a significantly greater Q max (20%) in the evening (9.6 mL/s) than in the morning (8.0 mL/s). Grino et al [7] reported marked variability in Q max between machine-read and manually read values, and attributed this to artefacts not recognized by the machine.…”
Section: Discussionmentioning
confidence: 99%
“…It is easily performed noninvasive and may allow quantitive data regarding voiding patterns [27]. Similar to ultrasound PVR, flow rates may be affected by operator error, benign prostate hyperplasia (BPH), lower urinary tract symptom, bladder dysfunction and variation in bladder capacity [28]. Further limitation of uroflowmetry include the needed for a minimum voided volume of 125 to 150 ml to reach a voided flow rate that reliably predicts an abnormality.…”
Section: Urethral Stricturementioning
confidence: 99%